Giả sử x0 là nghiệm của phương trình \(2.(x - 3) + 5x(x - 1) = 5x^2\). Chọn khẳng định đúng.

Câu hỏi :

Gọi x0 là nghiệm của phương trình \(2.(x - 3) + 5x(x - 1) = 5x^2\). Chọn khẳng định đúng.

A. x0>0

B. x0<−2

C. x0>−2

D. x0>−3

* Đáp án

D

* Hướng dẫn giải

 \(\begin{array}{*{20}{l}} {2\left( {x - 3} \right) + 5x\left( {x - 1} \right) = 5{x^2}}\\ { \Leftrightarrow 2x - 6 + 5{x^2} - 5x = 5{x^2}}\\ { \Leftrightarrow 5{x^2} - 5{x^2} + 2x - 5x = 6}\\ { \Leftrightarrow - 3x = 6}\\ { \Leftrightarrow x = - 2} \end{array}\)

Vậy  nghiệm của phương trình là \(x_0=−2>−3\)

Copyright © 2021 HOCTAP247